Strategies for clinical research on AIDS and HIV infection - Cattorini, Paolo; Mordacci, Roberto (Medicina e Morale, 1991)
Clinical research for new therapies for AIDS has raised particular ethical problems, especially in the United States. The need to quickly make available therapies which are at least able to extend the patients' life expectancy has questioned the scientific and ethical criteria of the contemporary regulations of drug experimentation. An interdisciplinary working group has therefore tried to suggest a series of recommendations for the basis of a new consent in this complex subject and we have published the document, translated into Italian, with an introduction and commentary for the Italian reader.